Prawne aspekty zakładania i prowadzenia działalności przez wstępnie uznane grupy oraz organizacje producentów owoców i warzyw - Suchoń, Aneta (Wydawnictwo Naukowe UAM, 2013)
This paper aims to evaluate the legal principles of establishing and running preliminarily recognised groups and organisations of fruit and vegetable producers after the amendments of the EU and Polish regulations. Among others, the approval principles of preliminary recognition (pre-recognition) and realisation of the recognition plans have been presented, followed by an analysis of membership agreements and the procedure of acquiring a status of a recognised organisation of fruit and vegetable producers. The supervision of those organisations by the province marshal as well as the financing of their activities using EU funds have been described. The paper ends with a conclusion that activities of preliminarily recognised groups and organisations of fruit and vegetable producers have been conducive to the development of the fruit and vegetable market in Poland. However, in order to make them even more efficient, the establishment procedures and the principles governing the running of groups and organisations of fruit and vegetable producers should be simplified, and legal instruments guaranteeing their greater stability introduced.

L’articolo si propone di valutare i principi giuridici della costituzione e il funzionamento dei gruppi e organizzazioni di produttori di frutta e verdura prericonosciuti dopo il cambiamento delle norme polacche e quelle dell’UE. In primo luogo è stata presentata la problematica del gruppo di produttori di frutta e verdura prericonosciuto, inclusa la questione di approvazione e realizzazione del piano di riconoscimento. Successivamente le considerazioni si sono incentrate sui contratti associativi e la procedura per ottenere lo status delle organizzazioni di produttori di frutta e verdura riconosciute, e in seguito sui controlli dei soggetti in esame svolti dal maresciallo del voivodato e del finanziamento della loro attività da fondi comunitari.In conclusione, l’autrice ha affermato che l’attività di gruppi e organizzazioni di produttori di frutta e verdura prericonosciuti ha contribuito allo sviluppo del mercato ortofrutticolo in Polonia. È tuttavia necessario semplificare le regole per la loro costituzione e lo svolgimento dell’attività. Inoltre, bisogna introdurre strumenti giuridici in grado di garantire una maggiore durabilità a questi soggetti.
Legal Aspects of Establishing and Running Preliminarily Recognised Groups and Organisations of fruit and Vegetable Producers After the Amendments of the EU and Polish Regulations
Aspetti Giuridici di costituzione e Svolgimento Dell'attivita da Parte di Grouppi e Organizzazioni di Produttori di Frutta e Verdura Prericonosciuti